PENINGKATAN KETERLIBATAN ALUMNI FISIPOL UNESA DALAM PENGISIAN TRACER STUDY - Fitri Norhabiba; Sri Murtini; Deby Febrian Eprilianto (Jurnal Pesona Nusantara, 2025)
Tracer studies are an important tool for universities to evaluate the relevance of their curriculum to the needs of the workforce. Unfortunately, alumni participation in completing tracer studies remains low, resulting in less than representative data. Therefore, efforts are needed to increase alumni engagement to ensure more accurate tracer study results and to improve educational quality. The goal of this activity is to increase alumni awareness and involvement in completing tracer studies and utilize the results for curriculum development and graduate quality improvement. Specific targets include increased alumni participation in completing tracer studies and more accurate tracer study data analysis that can be used for educational development. The method used is the formation of an active alumni community to encourage participation. All study programs consistently show progress in completing tracer studies each quarter. The Communication Studies Study Program held an alumni association formation event to facilitate alumni networking, alumni canvassing, and job vacancy information.